Electrical Energy Efficiency For Retroffitting Commercial Building - Lam, Sing Yew (2003)
The objective of this study is to reduce energy operating costs by introducing electrical energy conservation programmes such as improving lighting efficiency, reducing internal energy transmission losses along power cables and to replace inefficient equipment with energy efficient products for retrofit commercial buildings. Retrofitting commercial building has been defined as existing commercial building that will be undergoing major upgrading works such as replacing of wear and tear equipment and use products of new technologies or energy conservation techniques which can increase energy efficiency within the commercial building operation in order to remain competitive in operations. Energy conservation literature was reviewed and energy conservation techniques were implemented in a Malaysia Airlines System (MAS) headquarters building located at Lot 69, Section 57, Jalan Sultan Ismail, Kuala Lumpur. In this study energy analysis and inefficient usage of energy was determined by tabulating energy consumption and expenditure by referring to previous monthly electricity bills; monitoring of power consumption by computing variables such as power factor value, reactive energy and harmonic contents using (HIOKI) power monitoring meters and degree of luminance by determining luminaires system lux value using (HIOKI) Lux meter. Analysis of the energy data revealed that practical energy conservation programme techniques can be implemented to alleviate inefficient energy usage and reduction in operation cost. The results showed that by retrofitting the existing luminaires system to the recommended parabolic mirror reflector (PMR) luminaire and replacing the conventional bulb ' EXIT' sign luminaires to light emitting diode (LED) technology, inefficient usage electrical energy can be reduced and will lead to cost saving. The power factor correction method derived from analysis of practical energy data indicated that internal energy transmission losses over power cable can be reduced and also improve power system distribution capacity. The wear and tear of the existing electric motor can be replaced with energy efficient electric motor based on the energy consumption data comparison analysis. Improving the power quality problem especially the harmonic contents in the power system can also reduce electrical energy transmission losses by correcting the non-linear current distorted waveform. The conclusion that can be drawn here is that the electrical energy conservation programme techniques are indeed able to reduce the electrical energy consumption as shown by cost saving calculations.